ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI GIZI BURUK BALITA DI JAWA TENGAH DENGAN METODE SPATIAL DURBIN MODEL - Ikha Rizky Ramadani; Rita Rahmawati; Abdul Hoyyi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2013)
Severe malnutrition is a state of nutritional deficiencies at a severe level, where the nutritional status is far below the standard. Anyone can suffer from severe malnutrition, especially infants and children who are in the growth period. Central Java Province is one of many provinces in Indonesia where the cases of severe malnourished children under five years are high enough. It is noted that Central Java Province is one of 10 provinces in Indonesia with the highest rate of severe malnutrition cases for 6 years (2005-2010). Using data from year 2011, the result of the Moran’s I test states that there are spatial dependencies on severe malnutrition’s rate of children under five years and some of its influential factors on Central Java Province. Therefore, Spatial Durbin Model (SDM) method is used in this experiment. Variables which significantly affect severe malnutrition on Central Java Province through SDM method are : the numbers of infants with low birth weight ( ), the numbers of houses with good health status ( ), and the numbers of households with access to source of clean water ( ). SDM model obtains value of as much as 70.3% with AIC and MSE respectively 476.32 and 35280.11, results better than Ordinary Least Square (OLS) which produce as much as 41.5% with AIC 490.52 and MSE 60653.693